PERENCANAAN PAJAK, KOMITE AUDIT, NILAI PERUSAHAAN DAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2022)
This study aims to test whether tax planning affects firm value (H1), examine whether the audit committee affects firm value (H2), examine whether firm size affects firm value (H3), examine whether firm size moderates the effect of tax planning on firm value (H4), and examines whether firm size moderates the effect of the audit committee on firm value (H5). This study takes financial statement data from contractor and real estate companies listed on the Indonesia Stock Exchange for the period 2018 to 2020. The analysis used to test the hypothesis uses Moderated Regression Analysis (MRA) with the least squares method. The results of the analysis can be concluded that this study can accept and prove all the proposed hypotheses.
Keywords: Tax Planning; Audit Committee; Firm Value and Firm Size.